Предмет: Алгебра,
автор: Veronikaasmus
Вычислите значение производной данной функции в данной функции в точке x0
f(x)=x^4 - 2x^3 + x, x0= - 1
Ответы
Автор ответа:
24
f ' (x) = 4x^3 - 2*3x^2 + 1 = 4x^3 - 6x^2 +1
f ' (-1) = 4*(-1)^3 - 6*(-1)^2 + 1 = - 4 - 6 + 1 = - 10 + 1 = - 9
f ' (-1) = 4*(-1)^3 - 6*(-1)^2 + 1 = - 4 - 6 + 1 = - 10 + 1 = - 9
Похожие вопросы
Предмет: Математика,
автор: aleksandrdaminov
Предмет: Кыргыз тили,
автор: barktabasovguljeget
Предмет: Математика,
автор: chelovekrubik
Предмет: Математика,
автор: ymosentsev
Предмет: Алгебра,
автор: мари158